Pengaruh Penggunaan Hidrogen Peroksida (H2o2) Dengan Dosis yang Berbeda dalam Menekan Populasi Vibrio.Sp pada Tambak Udang Vannamei (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
Litopenaeus vannamei is a brackish-water aquaculture commodity that is highly favored by the Indonesian community and represents one of the country’s leading aquaculture products, with production continuing to increase in response to rising domestic and export demand. One of the main factors triggering disease in L. vannamei is the presence of Vibrio sp. bacteria, which are recognized as serious pathogens in various aquaculture organisms and serve as causative agents of bacterial diseases. These bacteria naturally inhabit marine environments and are categorized as opportunistic, meaning they become pathogenic when environmental conditions decline and host health is compromised. Disinfectants are chemical substances used to inhibit or eliminate microorganisms such as bacteria, viruses, and fungi (excluding bacterial spores) on non-living surfaces. One disinfectant material is Smart Care (Intracare B.V., The Netherlands), which contains stabilized hydrogen peroxide with a prolonged-release mechanism. This study employed an experimental method using a Completely Randomized Design (CRD) with four treatments and five replications. The treatments included a control (without H₂O₂) and applications of H₂O₂ at concentrations of 1 ml/L, 2 ml/L, 3 ml/L, and 4 ml/L. The results indicated that the addition of hydrogen peroxide at different concentrations did not produce statistically significant differences in suppressing the growth rate of Vibrio sp. Nevertheless, treatment C (3 ml/L H₂O₂) showed the highest inhibitory effect, with no bacterial colony growth observed. Therefore, the application of H₂O₂ at 3 ml/L demonstrates potential in reducing Vibrio sp. growth and supporting sustainable shrimp aquaculture practices.